2020
DOI: 10.1021/acschembio.0c00142
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Biochemical Analysis of Quorum Signal Synthase Specificities

Abstract: Many bacteria use membrane-diffusible small molecule quorum signals to coordinate gene transcription in response to changes in cell density, known as quorum sensing (QS). Among these, acyl-homoserine lactones (AHL) are widely distributed in Proteobacteria and are involved in controlling the expression of virulence genes and biofilm formation in pathogens, such as Pseudomonas aeruginosa. AHL molecules are specifically biosynthesized by the cognate LuxI type AHL synthases using S-adenosylmethionine (SAM) and eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Residue variations at these positions provided a relatively reasonable explanation for how AhyI can utilize non-native acyl-ACP substrates (C8~C14) with a limited acyl-chain pocket volume. A similar tunnel prediction had been recently verified by the observation of the increase in C 4 -HSL production and decrease in C 12 -HSL after a corresponding residue T105Y mutation in MplI [36]. Dong et al [19,36] showed that the acyl-substrate tolerance of some CoA-based LuxI synthases is likely to depend on the volume of binding pocket, because residues important for acyl group binding were occuping the position that branched or linear alkyl-group of acyl-CoA substrates would be in.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Residue variations at these positions provided a relatively reasonable explanation for how AhyI can utilize non-native acyl-ACP substrates (C8~C14) with a limited acyl-chain pocket volume. A similar tunnel prediction had been recently verified by the observation of the increase in C 4 -HSL production and decrease in C 12 -HSL after a corresponding residue T105Y mutation in MplI [36]. Dong et al [19,36] showed that the acyl-substrate tolerance of some CoA-based LuxI synthases is likely to depend on the volume of binding pocket, because residues important for acyl group binding were occuping the position that branched or linear alkyl-group of acyl-CoA substrates would be in.…”
Section: Discussionsupporting
confidence: 80%
“…Residue variations at these positions provided a relatively reasonable explanation for how AhyI can utilize non-native acyl-ACP substrates (C8 ~ C14) with a limited acyl-chain pocket volume. A similar tunnel prediction had been recently verified by the observation of the increase in C 4 -HSL production and decrease in C 12 -HSL after a corresponding residue T105Y mutation in MplI [ 36 ].
Fig.
…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations